Pengaruh Nilai Religiusitas, Pengetahuan Produk, Trend Fashion terhadap Minat Beli Fashion Pakaian Syar’i: Studi pada Wanita Muslim Pengguna Pakaian Syar’i di Kota Jakarta Selatan - Wanda Ana Fadilah; Muhaimin, Muhaimin; Intan Puspita Rini (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of religiosity, product knowledge, and fashion trends on purchasing interest, both partially and simultaneously. Amidst the rapid growth of the Muslim fashion industry, especially syar'i clothing, some consumers still consider fashion trends and popularity as the main considerations, while religiosity and product understanding are not yet the basis for decision making. This situation reflects a disparity between spiritual needs and current fashion trends. This is a quantitative study. The population in this study consists of Muslim women who wear syar'i clothing and reside in South Jakarta. The sample was taken using the Slovin formula with a total of 100 respondents. This study uses non-probability sampling techniques. Data collection in this study used questionnaires. The method used in this study was SEM-PLS using the Smart PLS 4 data analysis tool. The results of this study are as follows: (1) Based on the results of this study, it shows that each variable of religious values, product knowledge, and fashion trends has a significant positive effect, both partially and simultaneously, on purchasing interest. (2) The coefficient of determination (R²) value of 0.926 indicates a very strong level of influence. This figure indicates that 92.6% of the variability in purchase intention can be explained by the three main independent variables, namely religious values, product knowledge, and fashion trends. Meanwhile, the remaining 7.4% stems from the contribution of other variables not examined in this model.